2019
DOI: 10.2147/opth.s189183
|View full text |Cite
|
Sign up to set email alerts
|

<p>Transepithelial accelerated versus conventional corneal collagen crosslinking in patients with keratoconus: a comparative study</p>

Abstract: Purpose To systematically compare the efficacy of transepithelial accelerated corneal collagen crosslinking (TE-ACXL) with conventional corneal collagen crosslinking (C-CXL) in patients with progressive keratoconus. Methods Eyes of patients with progressive keratoconus who were treated with C-CXL (3 mW/cm 2 for 30 minutes) were compared with those who underwent TE-ACXL (6 mW/cm 2 for 15 minutes). Best-corrected visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
(77 reference statements)
0
17
0
Order By: Relevance
“…The median age was 24.00 years (range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and individuals in our sample were predominately men (76.3%). Median best corrected visual acuity (BCVA) was 0.90 Snellen (range 0.10-1.00), with glasses or contact lenses.…”
Section: Resultsmentioning
confidence: 86%
“…The median age was 24.00 years (range [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and individuals in our sample were predominately men (76.3%). Median best corrected visual acuity (BCVA) was 0.90 Snellen (range 0.10-1.00), with glasses or contact lenses.…”
Section: Resultsmentioning
confidence: 86%
“…In our study, stabilization occurred, but the results were not statistically significant, perhaps due to the shorter follow-up period (6 months). The results obtained by Madeira et al 10 were also statistically not significant over a follow-up period of 12 months.…”
Section: Discussionmentioning
confidence: 71%
“…8 Recent studies have concluded that the results of the standard and accelerated protocols are similar, including in children, although the results may vary considering irradiance, time and age, indicating the need for further studies to confirm the efficacy of the Accelerated protocol. 10,11 The objective of this study was to determine whether Accelerated CXL with UVA irradiation of 9 mW/ cm 2 for 10 minutes is as effective as standard CXL with UVA irradiation of 3 mW/cm 2 for 30 minutes in controlling the progression of keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…15,[22][23][24][25][26][27][28][29] In the present study, we evaluated the efficacy of TE-ACXL with a specific accelerated protocol (6 mW/cm 2 of UVA for 15 minutes); there is scarce published evidence. 21,23 Madeira et al had recently concluded that both TE-ACXL (6 mWcm 2 for 15 minutes) and C-CXL were similarly effective. 23 The current study does not find a significant difference in the visual acuity, as expected, since CXL is a treatment that aims at stopping disease progression and typically has a poorly marked effect on cornea shape.…”
Section: Discussionmentioning
confidence: 99%
“…21,23 Madeira et al had recently concluded that both TE-ACXL (6 mWcm 2 for 15 minutes) and C-CXL were similarly effective. 23 The current study does not find a significant difference in the visual acuity, as expected, since CXL is a treatment that aims at stopping disease progression and typically has a poorly marked effect on cornea shape. This is in agreement with the study done by Waszczykowska et al (accelerated CXL 6 mW/cm2 for 15 minutes), who report no significant improvement in visual acuity.…”
Section: Discussionmentioning
confidence: 99%